Wybrane piety w Małopolsce z okresu średniowiecza. Ich proweniencja, dzieje i wizerunek - Gołąb-Kowalska, Jolanta (Archiwa, Biblioteki i Muzea Kościelne, 2010)
The main purpose of this work is to present the provenance and the history of the chosen, characteristic and famous Pietàs from different works of art, monuments, and other buildings- for instance, churches, hospitals and roadside shrines. The vital issue of this article is to show the outward image of Pietàs. The author also focuses on analogies, similarities and differences in the image of Pietàs from Little Poland, and other regions and places which were outside Poland in the Middle Ages. This work concentrates only on the chosen Pietàs from different places such as Pietà from Limanów, Pietà in the church of the Nativity of the Holy Virgin Mary in Czchów, Pietà from Wojnicz, Pietà from Biecz (Mourning II), Pietà from the former Hospital for the Poor in Biecz, Pietà from Witkowice, Pietà from Szczyrzyc, Pietà from Dobczyce. The author chose these Pietàs, which despite coming from different places of Little Poland in the Middle Ages, best illustrate similarities and differences between each other and other sculptures. The paper also compares the analysed Pietàs with various sculptures and Pietàs from other regions of Poland and outside the country. Only certain of Pietàs are presented in this article, especially these which are described in different academic works and source materials. Some academic papers lack detailed information about the provenance, the history and the image of some of the gothic Pietàs from the Middle Ages in Little Poland. Only Pietà from Limanowa is the one about which there is thorough information in academic papers and source materials. So far, there has been no synthetic work or article about the provenance, the history and the overall image of Pietàs from Little Poland in the Middle Ages.